Kemampuan Komunikasi Matematis Siswa SMP melalui Model Problem Based Learning dengan Scaffolding E-LKPD Berdasarkan Self Efficacy - Nugraheni, Eunike Noor Adji; Shodiqin, Ali; Sutrisno, Sutrisno (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This study investigates the effect of the Problem-Based Learning (PBL) model assisted by scaffolding e-LKPD on the mathematical communication ability of eighth-grade students at SMP N 6 Jepara, analyzed based on their Self-Efficacy. Mathematical communication ability is crucial for students to understand processes, discussions, and decisions in mathematics , and low mathematical communication is associated with difficulties in solving mathematical problems. Self-efficacy is a factor that significantly influences students' mathematical problem-solving ability. This research used a Quasi-Experimental design with a Posttest Only Control Design. The sample was selected using a cluster random sampling technique, yielding two classes: Class VIII G as the experiment group (PBL model with scaffolding e-LKPD) and Class VIII F as the control group (conventional learning). The population for this study was all eighth-grade students at SMP N 6 Jepara during the 2025/2026 academic year. The research subjects were students from Class VIII SMP N 6 Jepara selected through random sampling. Pre-treatment data analysis confirmed that the two sample classes met the normality and homogeneity requirements. Final data analysis (posttest) using Two-Way ANOVA and Scheffe's follow-up test.